Intracoronary veratrine attenuates carotid baroreceptor reflex regulation of blood pressure in conscious dogs. - Denison, A L (1992)
1. The effect of activation of left ventricular cardiac receptors on carotid baroreflex control of blood pressure, heart rate, cardiac output, and total peripheral resistance was determined in conscious dogs. Previous studies in conscious subjects assessed only the effect on baroreflex control of heart rate. 2. Dogs with denervated aortic baroreceptors were equipped with aortic flow probes, cardiac pacing electrodes, and catheters in the aorta, vena cava, and left circumflex coronary artery. Both carotid sinus regions were prepared for reversible vascular isolation. 3. Left ventricular receptors were stimulated by an infusion of veratrine (0.1-1.0 micrograms kg-1 min-1) into the left circumflex coronary artery. 4. Veratrine infusion decreased control blood pressure only 10 +/- 2 mmHg, but it decreased the range of baroreflex control of blood pressure by 50% and decreased maximum baroreflex gain by 42%. Both the cardiac output and total peripheral resistance components of the baroreflex were attenuated. 5. Baroreflex control of blood pressure was unaffected by intravenous veratrine or by intracoronary infusion of vehicle. 6. Intracoronary veratrine had no effect after autonomic ganglionic blockade. 7. When cardiac output was kept nearly constant (by beta-adrenergic and cholinergic receptor blockade or by beta-blockade and cardiac pacing), intracoronary veratrine still attenuated baroreflex control of blood pressure and total peripheral resistance. Veratrine impaired the ability of the baroreflex to utilize alpha-adrenergic mechanisms to control total peripheral resistance. 8. We conclude that activation of ventricular receptors attenuates baroreflex regulation of blood pressure in conscious dogs through an attenuation of baroreflex control of both cardiac output and total peripheral resistance.